2009
DOI: 10.1097/pas.0b013e318184cd55
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Budding is a Strong and Reproducible Prognostic Marker in T3N0 Colorectal Cancer

Abstract: Tumor budding is a strong, reproducible, and independent prognostic marker of outcome that is easily assessed on hematoxylin and eosin slides. This may be useful for identifying the subset of T3N0M0 patients at high risk of recurrence who may benefit from adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
279
5
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(309 citation statements)
references
References 15 publications
20
279
5
5
Order By: Relevance
“…In one of the earlier studies of tumor budding, Hase et al 18 demonstrated that 5-year survival rates of Dukes B (stage II, T3-4 N0) patients with high-grade budding are significantly worse than those of Dukes C (N þ ) patients without budding (29 percent vs 66 percent; Po0.001). A number of more recent studies have confirmed that patients with Stage II colorectal carcinoma do significantly worse when high-grade budding is present, [34][35][36]38,41,45 and several studies have shown that survival rates of patients with Stage II colorectal carcinoma with high-grade budding are equivalent to survival rates of patients with Stage III colorectal carcinoma. [34][35][36] In their studies of Stage II and III pT3 tumors, Okuyama et al 34,35 found that tumor budding was the only factor on multivariate analysis to be associated with decreased survival and was more prognostically significant than lymph node metastases.…”
Section: Tumor Budding In Stage II (T3-4 N0) Colorectal Carcinomamentioning
confidence: 95%
See 3 more Smart Citations
“…In one of the earlier studies of tumor budding, Hase et al 18 demonstrated that 5-year survival rates of Dukes B (stage II, T3-4 N0) patients with high-grade budding are significantly worse than those of Dukes C (N þ ) patients without budding (29 percent vs 66 percent; Po0.001). A number of more recent studies have confirmed that patients with Stage II colorectal carcinoma do significantly worse when high-grade budding is present, [34][35][36]38,41,45 and several studies have shown that survival rates of patients with Stage II colorectal carcinoma with high-grade budding are equivalent to survival rates of patients with Stage III colorectal carcinoma. [34][35][36] In their studies of Stage II and III pT3 tumors, Okuyama et al 34,35 found that tumor budding was the only factor on multivariate analysis to be associated with decreased survival and was more prognostically significant than lymph node metastases.…”
Section: Tumor Budding In Stage II (T3-4 N0) Colorectal Carcinomamentioning
confidence: 95%
“…11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] On multivariate analysis, budding has consistently emerged as an independent adverse prognostic factor, associated with local tumor recurrence and distant metastases, and significantly worse overall and disease-free survival. 12,15,16,21,27,28,31,32,[34][35][36]38,40,41 The adverse prognostic impact of high-grade tumor budding is seen in both early and advanced colorectal carcinoma, and there are several scenarios in which this feature might influence clinical decision making, particularly in early colorectal carcinoma.…”
Section: Clinical Significance Of Tumor Buddingmentioning
confidence: 99%
See 2 more Smart Citations
“…The grade of each colonic adenocarcinoma was scored using a two-tiered scheme: low grade, 450% gland formation and high grade, o50% gland formation. Tumor budding assessment was performed using the rapid bud count method: 15 high budding, 450% of areas examined under  200 magnification were positive for budding and low budding, o50% of areas examined under  200 magnification were positive for budding. The presence of tumor-infiltrating lymphocytes was defined as 47 lymphocytes per 10 high-powered fields.…”
Section: Pathologic Evaluationmentioning
confidence: 99%